Penerapan Teknologi Augmented Reality sebagai Media Pembelajaran Fauna Berbasis Mobile Android - Trengginas, Way Lilo Tandang; Fachrie, Muhammad; Ardiani, Farida (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Fauna learning is a lesson that is commonly found in elementary school. Fauna learning is an important aspect of introducing fauna in Indonesia and the world. In this technological era, the limitations of learning media which still use conventional media such as books, text and images cause students' learning interest to decrease. This causes the ability to understand fauna to decrease and has an impact on low student learning outcomes. So this research aims to build an Augmented Reality (AR) based application that can be used as a media for learning fauna in elementary schools. The method used is the waterfall method, with this method the application is developed in stages starting from the analysis to design stages. Next, the resulting application is then tested using several testing methods, namely functionality testing, application performance testing and application feasibility testing with a questionnaire. Based on the test results, the application was successfully built where all functionality runs well. The application performance is also quite good where the marker can be detected at a distance of 10 – 70 cm with high, normal or low light intensity. The questionnaire results also showed good results, which means that the fauna learning application can be used easily and provides information that is easy to understand.